Slow-photon enhancement of dye sensitized TiO2 photocatalysis - A. Toumazatou; M. K. Arfanis; P.A. Pantazopoulos; A. G. Kontos; P. Falaras; N. Stefanou; V. Likodimos (Materials Letters, 2017)
Photonic band gap engineered TiO2 inverse opals were fabricated using self- assembled polystyrene films as sacrificial templates with controlled optical properties, aimed at the identification of the slow-photon effect on dye sensitized TiO2 photocatalysis. The materials’ photocatalytic efficiency was evaluated using Raman spectroscopy, on methylene blue photodegradation following both UVA and monochromatic visible light illumination. Contrary to UVA, where no photonic effect could be traced, laser irradiation within the slow-photon energy range of the TiO2 inverse opals, resulted in a marked increase of the dye photosensitized degradation rate, outperforming not only compact nanocrystalline films but also the benchmark mesoporous Aeroxide® P25 TiO2 films. This effect provides direct evidence for the presence of slow photons that amplify the interaction of visible light with the adsorbed dye molecules on the periodically structured TiO2 film.